High prevalence of ESBL‐producing Enterobacteriaceae carriage in Dutch community patients with gastrointestinal complaints. (3rd July 2012) - Reuland, E. A.; Overdevest, I. T. M. A.; al Naiemi, N.; Kalpoe, J. S.; Rijnsburger, M. C.; Raadsen, S. A.; Ligtenberg‐Burgman, I.; van der Zwaluw, K. W.; Heck, M.; Savelkoul, P. H. M.; Kluytmans, J. A. J. W.; Vandenbroucke‐Grauls, C. M. J. E.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract The aim of this study was to determine the rate of carriage of ESBL‐producing Enterobacteriaceae (ESBL‐E) in the community in the Netherlands and to gain understanding of the epidemiology of these resistant strains. Faecal samples from 720 consecutive patients presenting to their general practitioner, obtained in May 2010, and between December 2010 and January 2011, were analysed for presence of ESBL‐E. Species identification and antibiotic susceptibility testing were performed according to the Dutch national guidelines. PCR, sequencing and microarray were used to characterize the genes encoding for ESBL. Strain typing was performed with amplified fragment length polymorphism (AFLP) and multilocus sequence typing (MLST). Seventy‐three of 720 (10.1%) samples yielded ESBL‐producing organisms, predominantly E. coli. No carbapenemases were detected. The most frequent ESBL was CTX‐M‐15 (34/73, 47%). Co‐resistance to gentamicin, ciprofloxacin and cotrimoxazole was found in (9/73) 12% of the ESBL‐E strains. AFLP did not show any clusters, and MLST revealed that CTX‐M‐15‐producing E. coli belonged to various clonal complexes. Clonal complex ST10 was predominant. This study showed a high prevalence of ESBL‐producing Enterobacteriaceae in Dutch primary care patients with presumed gastrointestinal discomfort. Hence, also in the Netherlands, a country with a low rate of consumption of antibiotics in humans, resistance due to the expansion of CTX‐M ESBLs, in particular CTX‐M‐15, is emerging. The majority of ESBL‐producing strains do not appear to be related to the international clonal complex ST131.